Plasma Melatonin and Urinary 6-Hydroxymelatonin Levels in Patients with Pulmonary Tuberculosis - Ozkan, Esin; Yaman, Halil; Cakir, Erdinc; Deniz, Omer; Oztosun, Muzaffer; Gumus, Seyfettin; Erbil, Mehmet Kemal (Springer/Plenum Publishers, 2012)
Tuberculosis (TB) is the second most frequent cause of death in the world, after AIDS. Delay in diagnosing TB is an important worldwide problem. It seriously threatens public health. Cell-mediated immune responses play an important role in the pathogenesis of TB infection. The course of Mycobacterium tuberculosis (MTb) infection is regulated by two distinct T cell cytokine patterns. Melatonin is a biomolecule (mainly secreted by the pineal gland) with free radical scavenging, antioxidant and immunoregulatory properties. Melatonin has both its direct and indirect immunomodulatory effects on the immune system. In this study, we measured plasma melatonin and urine 6-hydroxy melatonin sulphate (6-HMS) concentrations in patients with newly diagnosed TB for the purpose of investigating whether there was a relationship between their levels and MTb infection. Thirty-one newly diagnosed patients presenting with active TB and 31 healthy subjects as the control group were included in this study. Blood and 24-h urine samples were collected from all individuals. Plasma melatonin levels and urine 6-HMS were measured. Our results show that in patients with TB, mean melatonin and 6-HMS concentrations were significantly lower than in the control subjects (p = 0.037, p < 0.001, respectively). We believe that the treatment of TB patients with melatonin might result in a wide range of health benefits including improved quality of life and reduced severity of infection in these patients. Supplementation with melatonin may be considered as an adjunctive therapy to classic treatment of pulmonary TB, especially during the acute phase of infection.
Keywords: melatonin; Mycobacterium tuberculosis; 6-hydroxy melatonin sulphate; pulmonary tuberculosis